Pengembangan Metode Pemulihan Penerimaan Pajak Pasca Pandemi Covid-19 - Mokhtar Sayyid; Rita Nataliawati (Owner : Riset dan Jurnal Akuntansi, 2022)
The case of the Covid-19 pandemic caused a slowdown in economic growth in Indonesia, which in turn resulted in a decrease in the amount of tax revenue, which eventually led the government to provide tax incentives to taxpayers. The COVID-19 pandemic has had a tremendous impact on all countries in the world, including Indonesia. The Central Statistics Agency (BPS) announced that the Indonesian economy experienced a slowdown in the first quarter of 2020, which was 2.97%. Compared to the fourth quarter of 2019, Indonesia's economic growth was recorded at minus 2.41%. This study aims to develop a method of tax revenue that has been adapted to the conditions of the Covid-19 pandemic. This study uses an exploratory method with a quantitative approach. The data used are the annual reports of companies listed on the Indonesia Stock Exchange (IDX) in 2018 and 2019. The sample selection method uses a purposive sampling method and obtained 233 samples for 2018 and 227 samples for 2019. With the results in the form of suggestions given in improving Post-covid-19 tax revenues, namely (1) Optimization of the withholding tax (WHT) mechanism, (2) Imposition of Final PPh for non-SME taxpayers, and (3) Efficiency of tax collection costs. This proposal requires in-depth study before implementation